2019
DOI: 10.18203/2320-6012.ijrms20191549
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of vitamin D deficiency in school children in Jammu: a whistle blower

Abstract: Background: Vitamin D deficiency prevails in epidemic proportions among school going children in India, but there is scarcity of searchable data on vitamin D status in school children in Jammu and Kashmir; hence we have assessed the vitamin D status in school going children attending outpatient department in a tertiary care hospital Jammu.Methods: The study was conducted in the department of Biochemistry Government Medical College Jammu during June to December, 2018 and after obtaining informed consent, a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…11 Study conducted by Kaur et al in Jammu, North India also found a high prevalence of vitamin D deficiency (87.5%) in school going children. 12 In accordance with this study, many studies have shown that despite having so many sunny days in India throughout the year, vitamin D deficiency is highly prevalent in our country irrespective of their age group and gender. [13][14][15][16] In a study conducted in North India (270N), 91% of healthy school girls were found to have hypovitaminosis D, findings similar to the results shown in our study.…”
Section: Discussionsupporting
confidence: 87%
“…11 Study conducted by Kaur et al in Jammu, North India also found a high prevalence of vitamin D deficiency (87.5%) in school going children. 12 In accordance with this study, many studies have shown that despite having so many sunny days in India throughout the year, vitamin D deficiency is highly prevalent in our country irrespective of their age group and gender. [13][14][15][16] In a study conducted in North India (270N), 91% of healthy school girls were found to have hypovitaminosis D, findings similar to the results shown in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Vitamin D deficiency is very prevalent in India. In our previous studies a very high prevalence of vitamin D deficiency along with other micronutrients has been observed in urban population of Jammu, comprising of pregnant women, 1 school going children 2 and elderly population of jammu. 3 The deficiency of Vitamin D, also known as sunshine vitamin, is very common in adolescents because of their changing life style, adaptation to western diet, decreased outdoor activities and more indulgence in indoor computer and internet games and less exposure to sunlight, As such vitamin D deficiency has assumed a pandemic proportions and is a major public health problem.…”
Section: Introductionmentioning
confidence: 88%